2011
DOI: 10.1037/a0020780
|View full text |Cite
|
Sign up to set email alerts
|

The team identification–social psychological health model: Sport fans gaining connections to others via sport team identification.

Abstract: Previous work has consistently found positive relationships between levels of sport team identification and social psychological well-being. According to the Team Identification-Social Psychological Health Model, these effects result from the increased social connections fans generate through their interest in the team. The current pair of investigations was designed to test the hypotheses that (1) team identification is positively related to social well-being and (2) team identification is positively related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 58 publications
7
85
0
Order By: Relevance
“…Accordingly, here we found out that importance of basketball in lives of top-class basketball players had a key role in their readiness and determination to establish relationships with teammates and other people. This finding is in accord with research which confirmed that team identification is positively related to social affiliation and the feeling of well-being [33].…”
Section: A Plan Of Analysissupporting
confidence: 82%
“…Accordingly, here we found out that importance of basketball in lives of top-class basketball players had a key role in their readiness and determination to establish relationships with teammates and other people. This finding is in accord with research which confirmed that team identification is positively related to social affiliation and the feeling of well-being [33].…”
Section: A Plan Of Analysissupporting
confidence: 82%
“…Research on social-psychological health demonstrates that team identification correlates with the number of temporary and enduring social connections a person shares with other consumers (Wann et al, 2011). However, this involves the formation of embedded relational groups within the superordinate identification.…”
Section: Limitationmentioning
confidence: 99%
“…Figure 1, relational groups depicted in B and C form through consumers sharing a common subgroup or superordinate identity, respectively. Sharing team identification fosters an increased number of temporary and enduring social connections with other team supporters (de Groot & Robinson, 2008;Wann, 2006;Wann et al, 2011). In a biographical study of one Australian Rules Football supporter, de Groot and Robinson (2008) noted that the study participant developed relationships with a larger network of Collingwood supporters on reaching the attachment stage of the Psychological Continuum Model (PCM) (Funk & James, 2001).…”
Section: Extended This Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this line of inquiry, team identification is a common construct in understanding sport fan behavior (Funk & James, 2001;Heere & James, 2007;Kwon, Trail, & Anderson, 2006;Matsuoka, Chelladurai, & Harada, 2003;Wann & Branscombe, 1993;Wann, Waddill, & Polk, 2011).…”
Section: Introductionmentioning
confidence: 99%